GlnR Dominates Rifamycin Biosynthesis by Activating the rif Cluster Genes Transcription Both Directly and Indirectly in Amycolatopsis mediterranei - Liu, Xinqiang; Liu, Yuanyuan; Lei, Chao; Zhao, Guoping; Wang, Jin (Frontiers in Microbiology, 2020)
Because of the remarkable efficacy in treating Mycobacterial infections, rifamycin and its derivatives are still first-line antimycobacterial drugs. It has been intensely studied to increase rifamycin yield from Amycolatopsis mediterranei, and nitrate is found to provide a stable and remarkable stimulating effect on the rifamycin production, a phenomenon known as "nitrate-stimulating effect (NSE)". Although the NSE has been widely used for the industrial production of rifamycin, its detailed molecular mechanism remains ill-defined. And our previous study has established that the global nitrogen regulator GlnR may participate in the NSE, but the underlying mechanism is still enigmatic. Here, we demonstrate that GlnR directly controls rifamycin biosynthesis in A. mediterranei and thus plays an essential role in the NSE. Firstly, GlnR specifically binds to the upstream region of rifZ, which leads us to uncover that rifZ has its own promoter. As RifZ is a pathway-specific activator for the whole rif cluster, GlnR indirectly upregulates the whole rif cluster transcription by directly activating the rifZ expression.Secondly, GlnR specifically binds to the upstream region of rifK, which is also characterized to have its own promoter. It is well-known that RifK is a 3-amino-5-hydroxybenzoic acid (AHBA, the starter unit of rifamycin) synthase, thus GlnR can promote the supply of the rifamycin precursor by directly activating the rifK transcription. Notably, GlnR and RifZ independently activate the rifK transcription through binding to different sites in rifK promoter region, which suggests that the cells have a sophisticated regulatory mechanism to control the AHBA biosynthesis. Collectively, this study reveals that GlnR activates the rif cluster transcription in both direct and indirect manners, which well interprets the phenomenon that the NSE doesn't occur in the glnR null mutant. Furthermore, this study deepens our understanding about the molecular mechanism of the NSE.